Value Chain Analysis of Prol Tape Cassava in Agroindustry in Jember - Sari, Fennela Firman; Anindita, Ratya; Koestiono, Djoko (HABITAT, 2017)
The purpose of the study was to analyze the mapping of prol tape value chain and the critical succes factor (CSF) to define effective strategyto improve the prol tape. The sampling methods were census and snowball sampling. The data analysis methods were mapping analysis, CSF, and benchmarking. The findings showed that the agroindustrial actors spent the highest amount of money in one production process, 2,278,999.75 rupiahs, and as the consequence got the least amount of profit, 862,292.25 rupiahs. According to the agroindustry, the most criticalfactors were taste, quality, and price, while those according to the consumers were taste, quality, and expired. The factor that had highest gap score was expired (0.97) followed by innovation (0.6) and supply (0.53). Therefore, the methods of upgrading to do were process upgrading (minimizing defects in raw materials), product upgrading (improving flavors, product diversification, mentioning expiration date and increasing supply), functional upgrading (increasing machine capacity for production) and chain upgrading (shifting the chain and not involving retailers, increasing the number of stores (outlets) in strategic locations, and buying raw materials directly from tape sellers).